PENERAPAN MODEL PEMBELAJARAN STEAM BERBANTUAN MEDIA VIDEO ANIMASI DALAM MENINGKATKAN HASIL BELAJAR IPAS SISWA DI KELAS IV SDN 1 BAJUGAN: penelitian tindakan kelas (PTK) - Sinta; Nasriani; Moh.Rudini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Sinta. 2025. Implementation of the STEAM Learning Model Assisted by Animated Video Media to Improve Science Learning Outcomes of Fourth-Grade Students at SDN 1 Bajugan. Thesis, Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Madako University, Tolitoli. Supervisor: Nasriani, S.Pd., M.Pd., Supervisor: Muh Rudini, S.Pd., M.Pd. This study aims to improve the science learning outcomes of fourth-grade students at SDN 1 Bajugan through the implementation of the STEAM learning model assisted by animated video media. This classroom action research was conducted in two cycles, each encompassing planning, action, observation, and reflection. The research subjects were 15 students. Data collection techniques used were observation, achievement tests, interviews, and documentation. The results of the study showed an increase in student learning outcomes, from an average of 64.6% in cycle I with a completion rate of 46.67% to an average of 85% in cycle II with a completion rate of 86.62%. Teacher and student activity also increased, with teacher activity reaching 89.5% and student activity reaching 91.66%. The implementation of the STEAM learning model was able to create a fun, interactive, and collaborative learning environment. These findings indicate that this learning model is effective in improving students' understanding of the material on the State of Matter and its Changes and can be used as an alternative learning strategy in elementary schools